Manajemen Mutu Layanan Ketatausahaan di MAN Wonogiri - Siska Kamilatuz Zakia; Fahrurrozi Fahrurrozi; Silviatul Hasanah (Jawda: Journal of Islamic Education Management, 2021)
Quality service is a service that always meets the needs and satisfaction of customers, namely school residents. In order to support the smooth learning process in schools, a part that supports activities is needed, namely school administration. The purpose of this study was to determine quality planning, quality control and quality improvement as well as input quality, process quality and output quality of administrative services at MAN Wonogiri. This study uses qualitative research, with descriptive methods through field studies conducted at MAN Wonogiri. The data acquisition using interviews, observation, and documentation. The results of this study indicate that (1) Quality planning at MAN Wonogiri includes several activities including planning meetings before the new school year by involving TU employees, TU heads and madrasa heads, determining customer needs and preparing evaluation plans. (2) Quality control is carried out by adjusting performance with objectives, evaluating and supervising madrasa administrative services, (3) Quality improvement is carried out by identifying improvements, making improvement efforts and programs to improve the quality of madrasa administrative services, (4) Input quality is supported by the ability education personnel who serve as well as adequate facilities and infrastructure, (5) The quality of the process is seen from the implementation of administrative services in the fields of education and teaching, finance, personnel and general affairs, (6) The quality of output is seen from the results of the performance of TU employees through the administrative self-evaluation of MAN Wonogiri.